2019
DOI: 10.3889/oamjms.2019.391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Quality of Life for Gynecologic Cancer Patients Using Functional Assessment of Cancer Therapy-General (Fact-G) Questionnaire at Haji Adam Malik Hospital

Abstract: BACKGROUND:Nowadays, successful treatment of cancer is not only measured by 5-years survival rate, but also by the patient’s quality of life (QOL). Delayed in the seeking of cancer treatment resulted in high morbidity and impact on the quality of life.AIM:This study aims to assess the QOL of patients with gynecologic cancer after therapy. The results of this research can be used as a basis for cancer treatment that should be holistic, not only to eradicate the disease, but also improve QOL.METHODS:A total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…Edianto et al assessed HRQOL in gynecologic cancer patients using FACT-G in an observational cross-sectional study. They did not find differences between treatment modalities, treatment duration and disease stage based on the total score of FACT-G [30].In their study most patients included had an early stage of the disease (57% stage I-II; 43% stage III; no patients with stage IV), in contrast to our study where most of the patients had a stage IV of the disease (77.7%), which could explain the differences regarding disease stage.…”
Section: Discussioncontrasting
confidence: 93%
“…Edianto et al assessed HRQOL in gynecologic cancer patients using FACT-G in an observational cross-sectional study. They did not find differences between treatment modalities, treatment duration and disease stage based on the total score of FACT-G [30].In their study most patients included had an early stage of the disease (57% stage I-II; 43% stage III; no patients with stage IV), in contrast to our study where most of the patients had a stage IV of the disease (77.7%), which could explain the differences regarding disease stage.…”
Section: Discussioncontrasting
confidence: 93%
“…It was determined that cancer treatment negatively affected the quality of life of the patients and that chemotherapy reduced the quality of life more than radiotherapy. Similar to our study, other studies found that the quality of life of patients who received radiotherapy was higher than those who received other treatments (Edianto et al, 2019; King et al, 2018; Reb & Cope, 2019). Tsai (2018) found that the quality of life scores of patients who received chemoradiotherapy after surgery were lower than those who received other treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, previous studies have shown that cancer treatment negatively affects the ability to maintain a social life (Pfaendler et al, 2015;Xiaoyun & Fenglan, 2020). The quality of life scores of patients who were receiving adequate familial and social support were better in other studies examining the quality of life of patients with gynecologic cancer (Edianto et al, 2019;Nazik et al, 2014;Pinar et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Participants’ QoL was measured with the Chinese version of the 27-item Functional Assessment of Cancer Therapy-General (FACT-G, version 4) [ 29 ]. The FACT-G has been used to evaluate the QoL of patients with GC across different cultures [ 30 , 31 ]. The FACT-G Chinese version has been proven as a valid instrument, with Cronbach α of .92 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%